(untitled) (Eurasian Scientific Herald, 2024)
This scientific article analyzes the civil law features of force majeure circumstances arising in artificial intelligence systems. Proposals have been developed on the procedure for determining liability for damage caused by artificial intelligence systems and on the grounds for excluding liability in the event of force majeure circumstances.